Negative Monetary Policy Rates and Portfolio Rebalancing : Evidence from Credit Register Data - Bottero, Margherita; Minoiu, Camelia; Peydro, Jose-Luis.; Polo, Andrea (Washington, D.C. : International Monetary Fund, 2019)
We study negative interest rate policy (NIRP) exploiting ECB's NIRP introduction and administrative data from Italy, severely hit by the Eurozone crisis. NIRP has expansionary effects on credit supply-- -and hence the real economy---through a portfolio rebalancing channel. NIRP affects banks with higher ex-ante net short-term interbank positions or, more broadly, more liquid balance-sheets, not with higher retail deposits. NIRP-affected banks rebalance their portfolios from liquid assets to credit-especially to riskier and smaller firms-and cut loan rates, inducing sizable real effects. By shifting the entire yield curve downwards, NIRP differs from rate cuts just above the ZLB.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet